LC-MS analysis, antioxidant and alpha-glucosidase inhibitory activities of Centaurea papposa extracts - Mawahib, Cheribet; Nabila, Zaabat; Nabila, Souilah; Chawki, Bensouici; Salah, Akkal (Bangladesh Journal of Pharmacology, 2019)
This work aimed to ascertain the phenolic compounds and assess the antioxidant capacity and alpha-glucosidase inhibitory activity of Centaurea papposa extracts. Phenolic compounds were appraised using LC-MS technique. Moreover, antioxidant activity was investigated using DPPH, ABTS, CUPRAC and FRAP assays. In vitro alpha-glucosidase inhibitory effect was carried out. LC-MS analysis revealed the presence of 21 compounds among which 13 were phenolic acids, 6 flavonoids, 1 phenolic aldehyde and 1 benzopyrone. The ethyl acetate extract exhibited the highest activity in ferric reducing antioxidant power (FRAP) assay (IC50: 22.9 ± 2.8 µg/mL). Nevertheless the n-butanol extract was the most active in cupric reducing antioxidant capacity assay (IC50: 3.1 ± 0.1 µg/mL). A significant alpha-glucosidase inhibitory activity was displayed by dichloromethane extract (IC50: 227.6 ± 4.4 µg/mL). Video Clip of Methodology: Cupric reduction antioxidant capacity: 1 min 47 sec: Click to watch